Developing Audio-Visual Speaking Material for Eighth Grade Students of SMP Negeri 1 Seram Barat - Lethulur, Dirk Valentino; Maruanaya, Hendrik (MATAI: International Journal of Language Education, 2025)
This research is grounded in the belief that well-designed speaking materials should integrate technology to create interactive, engaging, and meaningful learning experiences. To put this into practice, the researcher developed audiovisual speaking materials aimed at enhancing students' speaking proficiency and evaluated their effectiveness in the classroom. This study employs a Research and Development (R&D) model adapted from Borg and Gall (1983). The content and design of the materials were developed based on students’ learning needs and preferences identified through an earlier needs analysis. Various visual and audio elements were incorporated to create engaging and high-quality teaching videos. The materials then underwent an extensive review process, including expert evaluations, student feedback, and field testing. The study was conducted in a junior high school with a sample of 31 students. The results indicate that the audiovisual speaking materials effectively promote active student participation and enthusiastic engagement during exercises. Furthermore, the students' speaking proficiency significantly improved after the implementation of these materials.